2005
DOI: 10.2166/wst.2005.0667
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of aromatic surfactants from municipal wastewaters: comparison of conventional activated sludge treatment and membrane biological reactor

Abstract: Behaviour of anionic surfactants of linear alkylbenzene sulphonates (LAS) type and non-ionic surfactants of nonylphenol polyethoxylate (NPnEO) type was studied in the conventional mechanical/biological sewage treatment plant (STP) as well as using a membrane biological reactor (MBR). LAS and NPnEO were determined using high performance liquid chromatography (HPLC) equipped with spectrofluorimetric detection. Liquid chromatography/tandem mass spectrometry (LC/MS/MS) was used for identification and quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
4
18
0
3
Order By: Relevance
“…Satisfying degradation of investigated compounds was registered at high SRT of 30 d. In the same study it was shown that no significant difference is observed between the MBR and CTP in term of degradation performances. Similar observation on the removal of NP and BPA was described by Ivashechkin et al (2004a) during the operation of MBR and CTP processes at SRTs of 12 and 25 d. The high removal efficiency (95%) associated to the operation of high SRT in MBR was confirmed as well by Terzic et al (2005) concerning the removal of NPnEO from wastewater. Joss et al (2004) studied the E1, E2, EE2 degradation in batch experiment using sludge from CTP with SRT of 11 d and MBR with 30 d. For the natural estrogens E1 and E2, degradation activity seemed to be higher in MBR than in CTP by a factor of 2-3 with the respect to the applied SRT.…”
Section: Sludge Retention Time (Srt) and Biomass Concentrationsupporting
confidence: 86%
See 2 more Smart Citations
“…Satisfying degradation of investigated compounds was registered at high SRT of 30 d. In the same study it was shown that no significant difference is observed between the MBR and CTP in term of degradation performances. Similar observation on the removal of NP and BPA was described by Ivashechkin et al (2004a) during the operation of MBR and CTP processes at SRTs of 12 and 25 d. The high removal efficiency (95%) associated to the operation of high SRT in MBR was confirmed as well by Terzic et al (2005) concerning the removal of NPnEO from wastewater. Joss et al (2004) studied the E1, E2, EE2 degradation in batch experiment using sludge from CTP with SRT of 11 d and MBR with 30 d. For the natural estrogens E1 and E2, degradation activity seemed to be higher in MBR than in CTP by a factor of 2-3 with the respect to the applied SRT.…”
Section: Sludge Retention Time (Srt) and Biomass Concentrationsupporting
confidence: 86%
“…The removal of NPnEO and LAS from municipal wastewater was investigated (Terzic et al 2005). The results of this study showed removal efficiency up to 95% and the efficacy was in fact improved when the temperature in the treatment system varied from 3 to 30°C.…”
Section: 42mentioning
confidence: 93%
See 1 more Smart Citation
“…• Extended SRT as an Essence of Microbial Development and Biomass Quality A complete biotransformation of short-chain NPEOs, as aforementioned, may require a specialized microbial inoculum that could be enriched in an elevated SRT system [81,105,110,141]. According to Cirja et al [81], microbial communities including nitrifying bacteria are able to acclimate and develop at the SRTs of longer than 8 days.…”
Section: The Role Of the Secondary Activated Sludge Processmentioning
confidence: 99%
“…Como exemplo, os alquilbenzenos sulfonados de cadeia linear, conhecidos como LAS, apresentam longas cadeias alquídicas e, por isso, são preferencialmente encontrados adsorvidos no lodo (biomassa aeróbia ou anaeróbia); ao passo que os homólogos menores deste surfactante aniônico se encontram em maior concentração no efluente. 18 Dessa forma, efluentes de estações de tratamento de esgoto podem conter uma variedade de compostos orgânicos, e como o efluente tratado é, muitas vezes, despejado em mananciais de água potável, a poluição desta com contaminantes orgânicos é de grande preocupação. 19 Há vários estudos, feitos em outros países, mostrando que sistemas de tratamento biológico de esgotos não conseguem remover completamente compostos estrogênicos (ex., estradiol, estrona, etinilestradiol) capazes de alterar as funções endócrinas de animais aquáticos.…”
Section: Introductionunclassified